The Need To Use Game Technologies In Primary Education - Turdali Mukhtaraliyevych Sultanov (Academia One Publishing, 2023)
Working with students who are just beginning their studies in elementary school, teaching them, and achieving their behavioral development is a huge responsibility. In this, pedagogy is important because it provides teachers with insight into best practices for classroom organization. This allows them to understand how different students learn, so they can tailor their lessons to those needs. As a result, it increases the quality of their teaching because it is well received by students.
Keywords: primary education teachers; pedagogy; quality education